An Analysis on Responsibility as a Value in Physical Education Lessons in the University of Cienfuegos (CUBA) - Anairis Granado Mejías; Alexis Juan Stuart Rivero; Silvia Vázquez Cedeño; Carlos J. López-Gutiérrez (Publicaciones, 2017)
The aim of this study is to verify how some teachers take advantage or not, those modes of action of the value of responsibility manifested in physical education classes top level. An observation guide to classes was used, validated very adequate and reliable through 100% of the experts selected criteria. The observation guide was applied to teachers who have similar characteristics in terms of years of experience, teaching categories and scientific department of Physical Education, University of Cienfuegos in Cuba in the first half of 2015. The results evidence that teachers make good use of the behaviors that favor the fulfillment of the objectives of the classroom more, than those responsible behaviors that are collateral to these, so it can be concluded that the intention in this sense is not strong and there are significant gaps that must be valued.